Modeling and Validation of Electric Vehicle Drive Line Architectureusing Bond Graph - Rahman, Mohammed Ataur; Hasan, MD Nurul; Zaki, Mohd (The Mattingley Publishing Co., Inc., 2020)
An electric vehicle control technique (EV) can be systematically determined using Bond Graph. It is useful to determine the performance of the electric motor, inverter and battery when charging / discharging an electric vehicle separately. A simulated bond graph model shows how energy is transferred from one component to another of EV drive line. The bond graph simulation model is useful for optimizing the design of the EV powertrain and control in terms of charging / discharging, analyzing the behavior of the vehicle in both traction and cruising modes.Thus, the bond graph model helps to optimize the overall architecture of an electric vehicle driveline that could be crossed in all driving conditions. The purpose of this article is to present the behavior and characteristics of the bond graph on the simulation and optimization of an EV driveline. A bond graph simulation model is also used to analyze the EV drive cycle in terms of speed, traction, engine power, energy consumption, engine torque, voltage and battery charge/discharge current..The connectivity graph simulates the depth of discharge (DOD) of an EV battery and compares the simulated result with the laboratory and road test results. The simulated DOD was found to drop to 8% for EV when drive testing is considered for UDDS and 8.5% for HWFET. While it was 7.6% for the car in the laboratory and road tests. Thus, the bond graph Matlab-Simulink model can be validated and considered as an advanced tool for optimizing EV driveline architecture.